The miniaturized Raman system and detection of traces of life in halite from the Atacama Desert: some considerations for the search for life signatures on Mars - Vítek, Petr; Jehlička, Jan; Edwards, Howell G M; Hutchinson, Ian; Ascaso, Carmen; Wierzchos, Jacek (Astrobiology, 2012)
Raman spectroscopy is being adopted as a nondestructive instrumentation for the robotic exploration of Mars to search for traces of life in the geological record. Here, miniaturized Raman spectrometers of two different types equipped with 532 and 785 nm lasers for excitation, respectively, were compared for the detection of microbial biomarkers in natural halite from the hyperarid region of the Atacama Desert. Measurements were performed directly on the rock as well as on the homogenized, powdered samples prepared from this material-the effects of this sample preparation and the excitation wavelength employed in the analysis are compared and discussed. From these results, 532 nm excitation was found to be superior for the analysis of powdered specimens due to its high sensitivity toward carotenoids and hence a higher capability for their detection at relatively low concentration in bulk powdered specimens. For the same reason, this wavelength was a better choice for the detection of carotenoids in direct measurements made on the rock samples. The 785 nm excitation wavelength, in contrast, proved to be more sensitive toward the detection of scytonemin.
Keywords: fenoly; Phenols; minerály; Minerals; Indoles; mimozemské prostředí; Mars; indoly; Carotenoids; biologické markery; Biomarkers; Extraterrestrial Environment; karotenoidy; Spectrum Analysis, Raman; Ramanova spektroskopie